Modulating the properties of brown alga alginate-based fibers using natural cross-linkers for sustainable textile and fashion applications - Badruddin, Ishrat Jahan; Silva, Mariana P.; Tonon, Thierry; Gomez, Leonardo D.; Rahatekar, Sameer S. (American Chemical Society, 2024)
Seaweed-derived alginate shows promise in the textile industry as a sustainable alternative to synthetic and natural materials. However, challenges arise due to its low mechanical strength. We addressed this limitation by sustainably extracting alginates from European brown algae and employing novel manufacturing methods. Using natural cross-linkers, such as chitosan, ferulic acid, and citric acid, we have successfully modulated the mechanical properties of alginate fibers. Mechanical properties of ferulic acid and citric acid-cross-linked alginate solutions were spinnable, producing fibers with a diameter of 73–75 μm. Ferulic acid cross-linked alginate fibers exhibited stiffness, with a tensile strength of 52.97 MPa and a strain percentage of 20.77, mechanical properties comparable to those of wool, polyester, and rayon. In contrast, citric acid-cross-linked fibers showed partial elasticity, with a tensile strength of 14.35 MPa and a strain percentage of 45.53, comparable to those of nylon. This ability to control the mechanical properties of seaweed-derived fibers represents a significant advancement for their application in sustainable textiles and the fashion industry.
Keywords: 3403 Macromolecular and materials chemistry; 3406 Physical chemistry; 4004 Chemical engineering